Nutrient contents in camu-camu plants (Myrciaria dubia (Kunth) McVaugh) fertirrigateds with different doses of nitrogen - Abanto Rodríguez, Carlos (2018)
Camu-camu (Myrciaria dubia (Kunth) McVaugh) is a native fruit tree, which is in domestication process, therefore, knowledge of nutritional needs is essential to improve the fertilization efficiency throughout plant development. The aim of this research was to determine the nutrient content of camu-camu plants as a function of nitrogen fertilization via fertirrigation in the first year of cultivation. An experiment was carried out in a randomized complete block design, with 5 treatments as follows: 0; 40; 80; 120 and 160 kg.ha-1 of N, eight replicates and seven plants per experimental unit. The evaluated variables were as follows: total dry matter and nutrient contents in camu-camu leaves. The results show total dry matter of camu-camu plants, which were performed a significant quadratic behavior in response to increasing N doses. In Fact, N doses greater than 128 kg.ha-1 aroused a depressive effects. In addition, leaf contents of N, K, and Ca, had achieved a significant quadratic response and highest concentrations were recorded between 113 and 115 kg of N.ha-1. On the other hand, micronutrients had a polynomial depressive behavior according to an increasing N doses. It can be concluded that nutrient foliar contents are adequate for the camu-camu plants development. In fact, N, Ca, K, Fe, Mn and B, were the most required nutrients. Micronutrients determined in leaves, corresponded to the following decreasing order: N> Ca> K> Mg> S> P> Mn> Fe> B> Zn> Cu, respectively.